Find the best answers to your questions at Westonci.ca, where experts and enthusiasts provide accurate, reliable information. Our platform provides a seamless experience for finding reliable answers from a knowledgeable network of professionals. Get precise and detailed answers to your questions from a knowledgeable community of experts on our Q&A platform.
Sagot :
Answer:
Step-by-step explanation:
a² - b² = (a + b)(a - b)
x² - 16 = x² - 4²
= (x + 4)(x -4)
8 - 2x = (-2)*(-4) - 2x
= -2( -4 + x)
= -2( x - 4)
6(x² - 16) - (3x +1)(x - 4) + (8 - 2x) = 6(x +4)(x-4) -(3x +1)(x -4) - 2(x -4)
= (x -4) [6*(x+4) - (3x+ 1) - 2]
= (x -4) [ 6x + 24 - 3x - 1 - 2]
= (x - 4) [ 6x - 3x + 24 - 1 - 2]
= (x - 4)(3x + 21)
= (x -4) 3*(x +7)
= 3(x -4)(x+7)
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.